2006
DOI: 10.1111/j.1439-0507.2006.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candida species isolated from patients in intensive care unit and in vitro susceptibility to fluconazole for a 3‐year period

Abstract: Species level identification of Candida and antifungal susceptibility testing is not generally performed in routine laboratory practice. There is limited information about the distribution of Candida species and antifungal susceptibility in Turkey. In this study, we aimed at identifying Candida isolates to species level from various samples obtained from patients treated in an intensive care unit between 2002 and 2005 and to evaluate fluconazole susceptibilities of the isolates. A total of 320 Candida isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 16 publications
4
21
0
7
Order By: Relevance
“…yeasts were isolated: Trichosporon species and S.cerevisiae. C.albicans was the predominant species isolated in other studies (7)(8)(9)(10)(11)(12)(13)(14) which concurs with the findings in this study. The distribution of the non-albicans species, however, differed in different studies.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…yeasts were isolated: Trichosporon species and S.cerevisiae. C.albicans was the predominant species isolated in other studies (7)(8)(9)(10)(11)(12)(13)(14) which concurs with the findings in this study. The distribution of the non-albicans species, however, differed in different studies.…”
Section: Discussionsupporting
confidence: 83%
“…The ARTEMIS Global Antifungal Surveillance study demonstrated C.glabrata susceptibility in the range 29.2-100%; the isolates from S. Africa had a susceptibility of 49.6% (21.1% resistant). The MIC 90 of fluconazole for C.albicans in the current study (Table 2) was 1 µgml 1 (range: 0.25-8) which was similar to that obtained by Comert et al (range: 0.125-8) (14). The MIC 90 for C.glabrata in the current study was 32µgml -1 (range: 0.25-128) which was much higher than that for the same species in the study by Comert et al of 8µgml…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This diversity for Candida species has been frequently observed in prior studies. However, many comprehensive studies have shown the significant growth of the infections related to other non-Albicans Candida species (NACs) (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%